What Facilitates the Wait? Lessons Learned from Successful Sexual Abstainers. Issue 5 (19th October 2016) - Kosenko, Kami; Applewhite, Anastasia; Drury, Polina; Ash, Russell
Abstract : Religious individuals are more likely than their secular counterparts to abstain, but the explanatory mechanisms for religion's salutary effects on sexual and other health behaviors are poorly understood. Given that social support and other communicative processes are likely explanations for the religion–abstinence connection, this study was designed to determine what communication processes facilitate the wait for religious individuals. Interviews with 23 abstainers revealed that certain communication practices, such as avoiding temptations, creating networks of like-minded individuals, engaging in communal coping, establishing boundaries, finding role models, making social comparisons, and adhering to and enforcing injunctive norms enabled abstinence.